Religious Identity Negotiation in Japanese-Indonesian Intermarriage - Ulfah, Elisa (International Journal of Culture and Art Studies, 2023)
This research is qualitative research using a life story approach. The informants of this study were seven Indonesian Muslim women and one Christian who married a Japanese man living in Japan. The study analyzes how religious identity is negotiated in the marriages of Japanese men and Indonesian women. The previous research informants were three Indonesian women who married Japanese people in Indonesia. The prior research indicates that all Japanese husbands follow the religion of their Indonesian wives. This study finds that all Japanese husbands, before marriage, follow the religion of their Indonesian wives. Still, after marriage, some continue to follow the informant's religion, while others return to their previous religion. Seven informants kept their religion, but one person converted to the religion of a Japanese husband. Two informants entered marriages with different religions. One informant who did not want to follow her husband's religion had a severe conflict because of the intervention of the informant's mother-in-law. Husbands generally do not question the religion of their wives, but disputes arise in cases where Japanese husbands adhere to a particular religion. The Indonesian wife's family and several Japanese husband's families also intervened in the religious negotiations. The religious change of Japanese men before marriage is initially more of a consideration for the smooth running of the marriage process. Research on intermarriages between Indonesians and Japanese is minimal. Research likeÂ this needsÂ to be done because the number of intermarriages is increasing. This research brings valuable knowledge to prospective Indonesian and Japanese intermarriages.